Edukasi Penggunaan Gadget yang Sehat dan Aman bagi Kesehatan Mata Anak melalui Kader di Posyandu Wijaya Kusuma Kelurahan Palebon Semarang - Rochmayani, Dewi Sari; Cahyaningsih, Oktaviani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Technological developments cause children to increasingly use gadgets without adequate supervision, which poses a negative risk to children's physical health and psychological development. This Community Service (PkM) aims to empower Posyandu cadres in RW I Palebon Village, Pedurungan District, Semarang City as educational agents for the use of healthy and safe gadgets. The methods used include lectures, interactive discussions, simulations (role play), and field assistance. The results of the training showed an increase in cadre knowledge from 50.7 to 81.20 and cadre attitudes became very positive towards education on the use of gadgets. Cadres succeeded in conveying information well to parents, which also showed increased awareness of the importance of monitoring gadgets among children. This education is effective in increasing community knowledge and attitudes it is hoped that it can become a model of sustainable education to support optimal child growth and development at the RW level.